(untitled) (Environment & Health, 2020)
Objective: We substantiated the psychophysiological criteria for the diagnosis and psychohygienic correction of the educational stress in the students of modern higher medical educational institutions. Materials and methods: Scientific study was carried out on the basis of National Pirogov Memorial Medical University, Vinnytsia where 227 students aged 17 - 22 years were monitored. For an adequate implementation of the goal, a clearly structured set of highly informative psychophysiological and psychodiagnostic methods was used, as well as expert assessment method and method of statistical analysis. Results: The data obtained as a part of the performed study clearly confirm the fact that a number of psychophysiological criteria for diagnosis and psychohygienic correction of the adaptive possibility of the organism of the students of modern higher medical educational institutions under conditions of the educational stress should include: determination, taking into account, and assessment of the nature of the changes in the leading psychophysiological functions of the organism of the students of higher medical educational institutions in the dynamics of the academic year under conditions of constant educational stress; taking into account the data of psychophysiological analysis of the regularities of the changes in the leading personality features among the students of higher medical educational institutions during the academic year under conditions of constant educational stress; establishment of the nature of the changes of the leading characteristics of the functional possibilities of the organism and the features of psychophysiological adaptation of the students under conditions of pre-examination and examination situational educational stress; taking into account the data of the prognostic assessment of the peculiarities in the processes of psychophysiological adaptation among the students during the academic year and changes in its separate physiologically and mentally substantiated correlates among young girls and boys and the use of the methodology for the complex assessment of the level of expression of educational stress in the students of higher medical educational institutions both during the period of study and in pre-examination and examination periods. Conclusions: The psychophysiological criteria for diagnosis and psychohygienic correction of the educational stress in the students of modern higher medical educational institutions were defined and substantiated as a part of the study.